Seasonal Variation of Irrigation Water Quality in Bachok, Kelantan - Mohamed Hamim, Norlida; Shahrun, Mohammad Shahid; Jaafar, Jamaliah; Abdul Halim, Azhar; Juneng, Liew (International Journal of Integrated Engineering, 2025)
Agriculture is dependent on an adequate supply of suitable irrigation water quality. Physicochemical analysis of surface water for irrigation was conducted in Bachok, Kelantan during wet and dry period from July 2021 to December 2022. Surface water sampling points consist of primary, secondary and tertiary irrigation canals supplying water for paddy plantation. This study aimed to evaluate water quality trends in irrigation canals based on physicochemical parameters and discuss its pollution level and irrigation suitability using the Water Quality Index (WQI), National Water Quality Standards (NWQS) and irrigation suitability classification. It was observed that water quality was within NWQS Class IV except DO, Ammoniacal Nitrogen and TSS in locations with intensive aquaculture. ANOVA analysis showed a significant difference between water quality parameters and sampling locations (p<0.05). However seasonal variation in all irrigation canal’s water quality was statistically insignificant except for pH. WQI in all sampling points are between 55.86-93.71, which classified into the category of clean and adequate water. Irrigation water suitability index in Bachok are in the range of: SAR (0.31-1.75), MAR (22.75-57.3), SSP (25.9-68.78) and %Na (32.87-69.83). Results showed that half of the water sample in Bachok were slightly polluted and polluted according to WQI. Additionally, MAR and SSP classified 5% and 3% of water samples were unsuitable and unsafe for irrigation. Strategies must be developed to ensure pollution level remains below threshold.